2015
DOI: 10.1002/elan.201500120
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide/Carbon Nanotube/Gold Nanoparticles Nanocomposite Functionalized Screen‐Printed Electrode for Sensitive Electrochemical Detection of Endocrine Disruptor Bisphenol A

Abstract: We fabricated a highly sensitive electrochemical sensor for the determination of bisphenol A (BPA) in aqueous solution by using reduced graphene oxide (RGO), carbon nanotubes (CNT), and gold nanoparticles (AuNPs)‐modified screen‐printed electrode (SPE). GO/CNT nanocomposite was directly reduced to RGO/CNT on SPE at room temperature. AuNPs were then electrochemically deposited in situ on RGO/CNT‐modified SPE. Under optimized conditions, differential pulse voltammetry (DPV) produced linear current responses for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…This has also been observed in other studies reported in the literature. 18,46,47 Thus, it is necessary to remove the contaminated surface after each measurement. In this regard, electrodes based on carbon paste have an important advantage over film electrodes because a new surface is created simply by removing some of the paste, while the electrode film needs to be discarded after each measurement.…”
Section: Electrochemical Behavior Of Bpa At Mil/cpementioning
confidence: 99%
“…This has also been observed in other studies reported in the literature. 18,46,47 Thus, it is necessary to remove the contaminated surface after each measurement. In this regard, electrodes based on carbon paste have an important advantage over film electrodes because a new surface is created simply by removing some of the paste, while the electrode film needs to be discarded after each measurement.…”
Section: Electrochemical Behavior Of Bpa At Mil/cpementioning
confidence: 99%
“…Gold (Au)‐coated surfaces have an increasing interest in applications such as fuel cells, electrochemical sensing, electrochemical energy storage and catalysis . Gold nanoparticles (NPs) and Au thin films (TFs) are excellent candidates for HER electrocatalysts because they possess high catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] Gold (Au)-coated surfaces have an increasing interest in applications such as fuel cells, electrochemical sensing, electrochemical energy storage and catalysis. 24,25 Gold nanoparticles (NPs) and Au thin films (TFs) are excellent candidates for HER electrocatalysts because they possess high catalytic activity. 26,27 The coating of the Au nanostructures on the electrode increases the surface area and hence the adsorption capacity of the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The metal and semiconductor nanoparticles has gained enormous interest on the electrochemical interfaces to develop the electrochemical nanoscale systems for various catalytic and sensor applications (Alammari et al 2015;Keeley et al 2016;Wang et al 2016;Wang et al 2015). The metal nanoparticles play a key role in catalytic and electrocatalytic reactions which may empower numerous functionalities to line up for the targeted applications because of the interactivity of essential nanostructured sensor elements with their immediate local environments (Chen and Chatterjee 2013;Govindhan et al 2014, Huber et al 2015Maduraiveeran and Ramaraj 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The metal nanoparticles play a key role in catalytic and electrocatalytic reactions which may empower numerous functionalities to line up for the targeted applications because of the interactivity of essential nanostructured sensor elements with their immediate local environments (Chen and Chatterjee 2013;Govindhan et al 2014, Huber et al 2015Maduraiveeran and Ramaraj 2009). Especially, gold nanoparticles (Au NPs) have found use in areas ranging from chemical separations and sensing to direct applications in the medical, food, and environmental community due to their unique chemical, optical, and electronic properties (Huber and Leopold 2016;Moghimi et al 2015;Wang et al 2015;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%